Research of the effect of combined application of L-thyroxine (levotiroxine),doclofenac sodium and chondroitin sulphate on the histological structure of the cartilage tissue for hypothyroidism and osteoarthritis. - Nosivets, D. S.; Kosharniy, V. V.; Mamchur, V. I.; Opryshko, V. I. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. The study of thyroid pathology revealed the connection of this pathology with degenerative-dystrophic diseases of the musculoskeletal system. It is known that thyroid hormones affect the metabolism of cartilage and bone tissues and conditions are created for the development of osteoarthritis in the hypofunction of the thyroid gland. For correction of pathological changes in the clinical setting, L-thyroxine is prescribed for basic replacement therapy for thyroid hypofunction, however, developed osteoarthritis requires the use of NSAIDs and chondroprotectors, the purpose of which is governed by clinical protocols for the treatment of osteoarthritis. Objective. To investigate the effect of the combined use of L-thyroxine, diclofenac sodium and chondroitin sulfate on the histological structure of cartilage tissue in hypothyroidism and osteoarthritis in experimental animals. Methods. The work used 30 white adult outbred rats of both sexes weighing 220-230 g. Experimental modeling of hypothyroidism consisted in using a 0.02% solution of carbimazole (5 mg per 250 ml of saline) in the rats’ drinking diet for 6 weeks. Experimental osteoarthritis was reproduced by a single intra-articular injection of 0.1 ml of monoiodoacetic acid solution into knee joint of rats, which was prepared at the rate of 3 mg of reagent per 50 μl of sterile saline. The administration of drugs was carried out daily from the 42nd day of the experiment at the peak of an increase in pathological changes for 5 days. When the formation of experimental models was completed, animals were removed from the experiment by decapitation under thiopental anesthesia to study histo-morphological changes in the cartilage tissue of the knee joints. Results. Analysis of the histological structure of the cartilage of the knee joints of rats of experimental group number 3 showed that the cartilage and bone tissue of the knee joint of rats was almost the same in intact animals of group number 1 with the main parameters with the only difference that there was active regeneration of both cartilage and bone tissue with areas of neovascular genesis in group number 3. Conclusion. The studied effect of the combined use of L-thyroxine, diclofenac sodium and chondroitin sulfate on the histological structure of cartilage tissue in hypothyroidism and osteoarthritis in experimental animals established active regeneration of both cartilage and bone tissue with areas of neovascular genesis.